Strategic priorities of innovative development of construction industry enterprises - HAZUKIN, Andrii (Ways to Improve Construction Efficiency, 2025)
The article is devoted to substantiating the strategic priorities of innovative development for construction enterprises in Ukraine in the context of post-war reconstruction and the transition to the “Construction 4.0” paradigm. Its relevance is determined by the need for rapid infrastructure recovery, harmonization with EU standards, and enhancing the international competitiveness of the sector. The aim of the study is to develop theoretical and methodological approaches to identifying and hierarchizing innovation priorities and to propose practical mechanisms for their implementation. The methodological basis includes principles of strategic management and innovation economics, analysis of scientific publications, comparison with state reconstruction programs, and the logic of a systems approach. The generalization of results allowed identifying an interconnected set of priorities: technological modernization (BIM, digital twins, robotics, additive technologies), energy efficiency and “green” standards, digital transformation of project management (IoT, CDE, artificial intelligence), institutional and regulatory support, financial and investment instruments (PPP, grants, tax incentives), as well as human capital development (updating educational programs, training BIM managers, data engineers, and 3D printing operators). The novelty lies in forming an integrated system of strategic priorities adapted to Ukrainian realities, specifying expected effects and risks for each direction, and proposing an organizational and economic implementation mechanism (subjects, objects, principles, instruments, stages – preparatory, planning, implementation, control). The practical significance is the possibility of using the proposed mechanism as a “roadmap” for enterprises and regional authorities: it ensures transparent planning, a balance of funding sources, KPI system construction, integration of digital monitoring platforms, and decision-adjustment mechanisms. The conclusions confirm that the synchronous advancement of six priorities reduces time and budget losses from fragmented reforms, with critical success factors being stable financing, regulatory harmonization, and accelerated competency development.